Effectiveness of Laser Application for Periodontal Surgical Therapy: Systematic Review and Meta‐Analysis. Issue 12 (1st December 2015) - Behdin, Shabnam; Monje, Alberto; Lin, Guo‐Hao; Edwards, Bruce; Othman, Abdullah; Wang, Hom‐Lay
Abstract : Background: Evidence has shown some improved clinical outcomes and morbidity reduction with the use of lasers for non‐surgical periodontal therapy due to ablation, vaporization, hemostasis, and field sterilization. The purpose of this systematic review is to evaluate and compare studies involving lasers as monotherapy or adjunctive to surgical periodontal treatment. Methods: Electronic and manual searches were conducted by two independent reviewers in several databases for articles written in English up to December 2014. Articles were included in this review if they reported outcomes of surgical periodontal therapy with and without the use of lasers. The primary outcome was probing depth (PD), and secondary outcomes were measured changes in clinical factors such as clinical attachment level (CAL) and gingival recession (GR). For the comparative studies included, the pooled weighted mean difference (WMD) and 95% confidence interval (CI) of each variable were calculated using random‐effects meta‐analysis. Results: Eight and nine articles were included in the quantitative and qualitative analyses, respectively. Although low‐to‐moderate risk of bias was detected, high heterogeneity among studies was found. In flap surgery with or without laser treatment, there was no statistically significant difference in primary outcome. Similarly, in guided tissue regeneration (GTR)/enamel matrix derivative (EMD) with and without laser treatment, the WMD of PD was negligible; however, the GTR/EMD group showed better outcomes ( P = 0.005) than the laser group. Regarding the secondary outcomes, in the flap surgery group, the WMD of CAL gain was 1.34 mm, and the WMD of GR was −0.24 mm; no significant difference was detected between groups. In GTR/EMD with and without laser treatment, the WMD of CAL gain was 0.10 mm and the WMD of recession was −0.18 mm; again, no significant difference was detected between groups. Conclusions: The available evidence is insufficient to support the effectiveness of dental lasers as an adjunct to resective or regenerative surgical periodontal therapy. However, precautions must be exercised when interpreting the results of this study because of the small sample size and high heterogeneity among studies.